(untitled) (Africa Development, 1979)
CONTENTS - SOMMAIRE Regional Economic Integration and the Unequal Sharing of Benefit: Background to the Disintegration and Collapse of the East African Community NGILA MWASE ........................... 1 Le Role du Secteur Public dans la Tradition du Socialisme : Le cas Algérien M. S. BEDRANI ........................ 30 State Capitalism: The Role of Parastatals in Zambia BEN TUROK ............................ 44 Tentatives de Stabilisation Economique au Zaire KANSONGO MUNGANGA ................. 68 Enlangling Alliance: Black Americans, Africa and Capitalism MAGHAN KEITA .......................... 92 A Review of the Political Economy of the Industrialisation Strategy of the Nigerian State, 1960—1980 AKIN FADAHUNSI .......................... 106 Le Problème de la Réforme Agraire en Afrique au Sud du Sahara M. L. GAKOU ............................ 126 Le Développement du Capitalisme Agraire et l'Expérience de Petits Planteurs à l'Ile Maurice RAJ VIRAHSAWUY ...................... 136 PRESENTATION : The Role of the Institute of Development Research (University of Addis Ababa).